Key Factors of Combustion From Kinetics to Gas Dynamics - Rubtsov, Nikolai M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book summarizes the main advances in the mechanisms of combustion processes. It focuses on the analysis of kinetic mechanisms of gas combustion processes and experimental investigation into the interrelation of kinetics and gas dynamics in gas combustion. The book is complimentary to the one previously published, The Modes of Gaseous Combustion.
Nonlinear phenomena and kinetic mechanism of a gaseous branching chain process by the example of thermal decomposition of nitrogen trichloride -- Nonlinear effects in silanes oxidation and chlorination in gaseous phase: collecting a puzzle -- Electric phenomena in silanes chlorination and oxidation -- Excited intermediates in silanes combustion -- Reactions of hydro peroxide radicals in hydrogen combustion -- Flame acceleration in reactive gas flows -- Influence of hydrocarbon additives on the velocity of detonation wave and detonation limits by the example of the reaction of hydrogen oxidation.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Physical chemistry; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Physical Chemistry